Pursuing Quality Education in Karamoja. An Analysis of the Caregivers’ Quality Indicators from a Community Perspective for Sustainable Early Childhood Education Programmes - Apolot, Josephine Matha; Ejuu, Godfrey; Lubaale, Grace (American Journal of Education and Practice, 2020)
Purpose of the study: The purpose of the study was to analyze the caregivers' quality indicators from a community perspective for sustainable ECE programmes. Methodology: The study employed a qualitative approach that used phenomenology research design. Twenty-five interviews and ten focus group discussions were used on the respondents for collecting data. The data collected from the caregivers/teachers, elders, parents and Early Childhood Education focal point officers revealed that the Ministry of Education and Sports caregiver quality indicators are not much emphasised in Karamoja. Findings: While the ECE learning framework wants caregivers to promote holistic development of children, the karimojong community wants caregivers to focus more on their culture. A good ECE caregiver for Karamoja should be able to honour the histories, culture, language, traditions, child rearing practices and lifestyle choices of the communities. Unique contribution to theory practice and policy: The findings indicate that there is need for stakeholders to work together to identify the caregivers ECE quality indicators then support in the designing, implementation and supervision of the ECE programmes for sustainability. If researchers use the strengths of communities, enshrined in their funds of knowledge, we are more likely to tap into their reserve support for ECE interventions. The social capital theory therefore when correctly implemented helps the caregivers and the education sector in working collaboratively with the parents in the setting up systems that aim at sustainable ECE programmes in the communities.